Searching for stop LSP at the LHC - Essodjolo Kpatcha; Iñaki Lara; Daniel E. López-Fogliani; Carlos Muñoz; Natsumi Nagata; Hidetoshi Otono (European Physical Journal C: Particles and Fields, 2022)
Abstract We analyze relevant signals expected at the LHC for a stop as the lightest supersymmetric particle (LSP). The discussion is carried out in the framework of the $$μ ν $$ μ ν SSM, where the presence of R-parity violating couplings involving right-handed neutrinos solves the $$μ $$ μ -problem and reproduces neutrino data. The stops are pair produced at the LHC, decaying with displaced vertices to a lepton and a bottom quark or a neutrino and a top quark. We compare the predictions of this scenario with ATLAS and CMS searches for long-lived particles. To analyze the parameter space we sample the $$μ ν $$ μ ν SSM for a stop LSP using a likelihood data-driven method, and paying special attention to reproduce the current experimental data on neutrino and Higgs physics, as well as flavor observables. Our results translate into a lower limit on the mass of the left (right) stop LSP of 1068 GeV (1341 GeV), corresponding to a decay length of 1.86 mm (6.61 mm).